2022
DOI: 10.12669/pjms.38.5.5230
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of Vortioxetine and escitalopram in the treatment of depression

Abstract: Objectives: This study was aimed to investigate the efficacy and safety of vortioxetine hydrobromide in the treatment of major depressive disorder (MDD). Methods: One hundred and eighty patients with the newly diagnosed depression in our hospital between August 2018 and August 2019 were selected and randomly divided into an observation group and a control group, 90 each group. The control group was treated with escitalopram, and the observation group was treated with voltaxetine. The efficacy and adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
1
0
0
Order By: Relevance
“…Similarly, patients reported significant improvements in cognitive function via both DSST and PDQ-K. These results echoed the significant improvements in clinical symptoms and patient reported cognitive function reported in RCTs and/or real-world studies of vortioxetine (19,25,26,33,35,36).…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, patients reported significant improvements in cognitive function via both DSST and PDQ-K. These results echoed the significant improvements in clinical symptoms and patient reported cognitive function reported in RCTs and/or real-world studies of vortioxetine (19,25,26,33,35,36).…”
Section: Discussionsupporting
confidence: 53%
“…Some of these studies (n = 5) found vortioxetine to be superior in mood symptom reduction than the active comparator, including agomelatine [43,44], venlafaxine [45], desvenlafaxine [46] and duloxetine [47]. Other experiences (n = 4) found vortioxetine to be more effective in cognitive symptom reduction with respect to escitalopram, paroxetine, and duloxetine [48][49][50][51]. Half of these trials (n = 11) found no significant difference between vortioxetine compared to sertraline [52], venlafaxine [53,54], desvenlafaxine [55,56], escitalopram [55][56][57][58], vilazodone [57], and duloxetine [59][60][61][62], although duloxetine tended to perform better in these studies.…”
Section: Experimental Studiesmentioning
confidence: 99%